Cuándo comienza la historia de Israel en la antigua Palestina? Apuntes para una discusión - Pfoh, Emanuel (2015)
Since its discovery in 1896, the so-called Victory Stele of Pharaoh Merenptah (ca. 1209/8 BCE) has been considered the first extra-biblical mention of the term "Israel" in the ancient Near Eastern epigraphic repertoire. This mention has also been used both to give a certain ethnic identity to the dwellers of Palestine's highlands during the 12th-11th centuries BCE and to confirm, to a certain extent, the historicity of the Old Testament narrative. In this paper, this question is revised in order to reconsider the semantics of this term and its relation to Israelite origins and the beginnings of Israel's history in the ancient Near East. Problematizing the term "Israel" is also in order, as an ethnic, socio-political and religious referent. Such a perspective allows for advancing a non-essentialist interpretation of what "Israel" was in ancient Palestine, according to a variety of identity references.